2014
DOI: 10.1002/joc.3916
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the CMIP5 global climate model simulations of the western tropical Pacific climate system and comparison to CMIP3

Abstract: A set of 27 global climate models from the Coupled Model Inter-comparison Project Phase 5 (CMIP5) ensemble are assessed for their performance for the purpose of making future climate projection studies in the western tropical Pacific and differences to Coupled Model Inter-comparison Project Phase 3 (CMIP3) are assessed. The CMIP5 models show some improvements upon CMIP3 in the simulation of the climate in the western tropical Pacific in the late 20th century. There are fewer CMIP5 models with very poor skill s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 51 publications
4
58
0
Order By: Relevance
“…Currently, coupled climate models do not yet have a perfect representation of various modes of climate variability, such as the El Niño-Southern Oscillation (ENSO) or the Pacific decadal oscillation (PDO). However, the simulation of the western tropical Pacific climate variability and processes has improved for the new generation of climate models (CMIP5) with respect to the CMIP3 generation (e.g., Bellenger et al 2014;Grose et al 2014). In addition, Monselesan et al (2015) showed that, for sea level and sea surface temperature, the spatiotemporal characteristics of the variances over various frequencies or bands in the CMIP5 control runs and the observations are in reasonable agreement for those periods and regions where there are reliable observations.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, coupled climate models do not yet have a perfect representation of various modes of climate variability, such as the El Niño-Southern Oscillation (ENSO) or the Pacific decadal oscillation (PDO). However, the simulation of the western tropical Pacific climate variability and processes has improved for the new generation of climate models (CMIP5) with respect to the CMIP3 generation (e.g., Bellenger et al 2014;Grose et al 2014). In addition, Monselesan et al (2015) showed that, for sea level and sea surface temperature, the spatiotemporal characteristics of the variances over various frequencies or bands in the CMIP5 control runs and the observations are in reasonable agreement for those periods and regions where there are reliable observations.…”
Section: Methodsmentioning
confidence: 99%
“…The representation of rainfall and the atmospheric circulation over the Maritime Continent is particularly poor in GCMs, and errors are apparent in both coupled and atmosphere-only climate model simulations (Flato et al 2013;Grose et al 2014). In coupled models, including the Met Office Unified Model (MetUM), precipitation rates tend to be overestimated over the Maritime Continent, primarily as a result of a cold tongue SST bias in the Pacific (Irving et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this critical region of anomalously fast sea level-rise, the rise rate can be modulated by decadal to multi-decadal variability related to the low frequency Southern Oscillation Index (SOI) and Pacific Decadal Oscillation (PDO) [11]. In general, CMIP5 models show improved performance over CMIP3 in the western tropical Pacific, but continue to show significant biases in both mean state and variability [12]. This currently presents a challenge in predicting future SLR especially for vulnerable island nations of this region.…”
Section: Introductionmentioning
confidence: 99%